Two Cases of Pulmonary Alveolar Microlithiasis in a Family (Journal of Medicine, 2013)
Pulmonary alveolar microlithiasis is a disease of unknown etiology. The disorder affects people at every age beginning from the early childhood. It usually occurs in a sporadic form, but an autosomal recessive form has been described, especially in patients from the Mediterranean countries. Our cases were in one family. A 44 years old man and his younger(35 years old) sister. Both of them complaint of dyspnea, bluish discolouration of face and extremities (acrocyanosis), clubbing, and coughing We evaluate both of them. These are findings in the male patient, and his sister had very similar findings. CXR and CT scan findings imply that we had 2 case of pulmonary alveolar microlithiasis (PAM). DOI: http://dx.doi.org/10.3329/jom.v14i1.14583 J MEDICINE 2013; 14 : 80-82